Water Consumption Comparison Between a Natural Draft Wet Cooling Tower and a Natural Draft Hybrid Cooling Tower—An Annual Simulation for Luoyang Conditions. Issue 11 (13th August 2017) - Xia, Lin; Li, Jishun; Ma, Wei; Gurgenci, Hal; Guan, Zhiqiang; Wang, Pei
ABSTRACT: The Merkel method, the Poppe approach, and an empirical equation are employed in the developed computer program to predict the evaporation loss for the natural draft wet cooling tower (NDWCT). All the three models are validated with the experimental results. The calculation results in the NDWCT of a 300-MW power plant in Luoyang show that both the Merkel method and the empirical equation could not make the accurate evaporation loss prediction as the Poppe approach does. The annual water consumption and economic benefits for the power plant employed with the NDWCT and the natural draft hybrid cooling tower (NDHCT) are calculated by using the hourly weather condition. The results show that the power plant would save more than 95% of water but lose US$15, 464, 306 per year by replacing the NDWCT with the NDHCT.